Safety of cassia gum as a feed additive for cats and dogs based on a dossier submitted by Glycomer GmbH - Bampidis, Vasileios (EFSA J, 2019)
The additive cassia gum consists mainly of high‐molecular weight polysaccharides composed primarily of a linear chain of 1,4‐β‐d‐mannopyranose units with 1,6‐linked α‐d‐galactopyranose units. In 2014, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) delivered an opinion on the safety and efficacy of cassia gum in cats and dogs. The Panel concluded, based on positive findings observed in a bacterial reverse mutation test with a semi‐refined cassia gum (about 70 mg anthraquinones/kg) but not with purified semi‐refined cassia gum that meets the specification as a food additive (< 0.5 mg anthraquinones/kg), that only purified semi‐refined cassia gum that meets the specifications of cassia gum as a food additive can be considered safe for cats and dogs, at a maximum content of 1.5% cassia gum (15,000 mg/kg feed) in dry matter, corresponding to 1.32% (13,200 mg/kg feed) in a standardised complete feed with 12% water content. The conclusion was confirmed in an opinion delivered by the Panel in 2017. Following this opinion, the European Commission gave the possibility to the applicant to submit complementary information on the safety for cats and dogs. The semi‐refined cassia gum under application was mutagenic in a bacterial reverse mutation test in Salmonella Typhimurium strain TA100. Positive results were also observed after heat sterilisation of the test item. Isopropanol purified semi‐refined cassia gum did not show mutagenic effect. Examination of various other cassia gum extracts did not identify any source of mutagenicity. The mutagenicity of the semi‐refined cassia gum under application cannot be excluded. Therefore, the FEEDAP Panel cannot establish the safety of semi‐refined cassia gum for cats and dogs.